Population distribution patterns of Nepenthes reinwardtiana Miq. in Kerangas Forest of Teluk Adang Nature Reserve, Paser Regency - Ratna Juliarti Wulandari Wulandari; Muhammad Sumaryono; Ali Suhardiman (Foresty Faculty of Hasanuddin University, 2020)
Teluk Adang Nature Reserve (NR) is one of the Nepenthes habitats in East Kalimantan. One of the four Nepenthes species that can be found in this nature reserve is Nepenthes reinwardtiana or by local people known as anjat datu. The objectives of this study are to determine the population of N. reinwardtiana in Teluk Adang NR by calculating its density and frequency, and to know its distribution pattern using Morisita index and spatial analysis approach in the form of Nearest Neighbor Analysis and Multi-Distance Spatial Cluster Analysis (Ripley's K Function). To know its distribution pattern, a census method by creating 5m x 5m plot along the observation track was done. The results showed that there were 2,943 individuals of N. reinwardtiana in Teluk Adang NR. Standardized Morisita Dispersion Index was 0.51, 0.55, and 0.51 in Tajur Village, Pasir Mayang Village, and Janju Village, respectively. The spatial distribution of N. reinwardtiana was clustered. Research on the distribution of N. reinwardtiana and its habitat needs to be carried out continuously so that its population in the Teluk Adang NR can be monitored.